The implications of punishment. An ethnographic study in a wom's prison in Argentina - Ojeda, Natalia S. (2017)
Starting from an ethnographic perspective, the data that support the development of the article are part of a research project that had as a general objective, to account for the complexity and sense of confinement in a women’s prison belonging to the Argentine Federal Penitentiary Service (SPF). From this perspective, the jail is understood as a particular type of social system, where punishment and penalty are administered, but also constantly redefined itself from the complex social relationships that constitute it. This article is intended to account for such complexity by showing how affectivities are part of punishment administration, redefining not only their senses but also the own experience of prison.